An index based searchable encryption scheme with IND-CCA security - Nateghizad, Majid (2014)
Cloud computing offers a wide range of services such as user demand network, operating systems, hardware, software and resources. These encouraging facilities and hassle free management of computing resources have attracted many users to outsource their data to untrusted servers. In addition, encrypting documents prevents user to search the outsourced documents directly. Regular encryption algorithms such as AES, RC4 and DES mechanisms have searching limitation; in which the whole ciphertext needs to be retrieved and then decrypt before search procedure can be performed. However, searchable encryption algorithms suffer from security and search performance problems. Hence, none of proposed searchable encryptions is not based on IND-CCA2 security level; they are not secure against adaptive chosen ciphertext attacks. Furthermore, the search performances of proposed searchable encryption algorithms that are index based or bloom filter based do not satisfy the search performance in terms of false positive rate and search cost equal. In this study, three searchable algorithms are proposed Index Based Search Encryption with Low False Positive Rate (ISELFP), Secure Searchable Based Asymmetric Encryption (SSAE), and Index Based Secure Searchable Asymmetric Encryption (ISSAE)